2019
DOI: 10.3847/2041-8213/ab4ae1
|View full text |Cite
|
Sign up to set email alerts
|

A NICER Thermonuclear Burst from the Millisecond X-Ray Pulsar SAX J1808.4–3658

Abstract: The Neutron Star Interior Composition Explorer (NICER) has extensively monitored the August 2019 outburst of the 401 Hz millisecond X-ray pulsar SAX J1808.4-3658. In this Letter, we report on the detection of a bright helium-fueled Type I X-ray burst. With a bolometric peak flux of (2.3 ± 0.1) × 10 −7 erg s −1 cm −2 , this was the brightest X-ray burst among all bursting sources observed with NICER to date. The burst shows a remarkable two-stage evolution in flux, emission lines at 1.0 keV and 6.7 keV, and bur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 50 publications
11
60
1
Order By: Relevance
“…Similar excesses have been seen in Type I bursts in many other sources observed with NICER, e.g. Aql X-1 (Keek et al 2018a), 4U 1820-30 (Keek et al 2018b) and SAX J1808.4-3658 (Bult et al 2019). This could be due to other extra components such as re-emission from the disc (corresponding to the extra black body, Keek et al 2018a) or enhanced accretion through Poynting-Robertson drag (corresponding to the change in persistent emission normalisation, Worpel et al 2013).…”
Section: Time Resolved Spectroscopysupporting
confidence: 81%
See 1 more Smart Citation
“…Similar excesses have been seen in Type I bursts in many other sources observed with NICER, e.g. Aql X-1 (Keek et al 2018a), 4U 1820-30 (Keek et al 2018b) and SAX J1808.4-3658 (Bult et al 2019). This could be due to other extra components such as re-emission from the disc (corresponding to the extra black body, Keek et al 2018a) or enhanced accretion through Poynting-Robertson drag (corresponding to the change in persistent emission normalisation, Worpel et al 2013).…”
Section: Time Resolved Spectroscopysupporting
confidence: 81%
“…Additionally, helium fuelled bursts are also more common during the soft accretion state and the dip in apparent radius below the final value is more typical of soft state bursts (Kajava et al 2014). Further, bursts can reach the Eddington limit for helium even where accreted material is hydrogen rich, either by the hydrogen being burnt between bursts or the hydrogen rich atmosphere being blown off by the burst (Bult et al 2019;Galloway et al 2006). This would imply that the further distance estimates (blue curves in Figure 7) are more likely (12.8 +0.7 −0.6 kpc for i = 80 • ).…”
Section: Distance Estimate and Implicationsmentioning
confidence: 99%
“…Moreover, significant soft excesses with respect to the hardstate persistent emission were measured in the burst spectra of EXO 0748-676 (Asai & Dotani 2006), SAX J1808. 4-3658 (in 't Zand et al 2013;Bult et al 2019), and Aql X-1 (Keek et al 2018). These excesses suggest a temporary enhancement of the accretion rate induced by the burst, probably via Poynting-Robsertson drag of the accretion flow (Ballantyne & Everett 2005).…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, S1 showed burst oscillations. Bult et al (2019) found that the pause, the dip between the X-ray burst's double peaks, and the onset of burst oscillations all occur at similar count rates, suggesting that the similar count rates are related to the Eddington limit of a hydrogen envelope.…”
Section: Pauses and Comparisonmentioning
confidence: 86%
“…what we observe as a pause is in reality a very short, weak peak of a double-peaked X-ray burst), or the pause is unrelated to the physical process that produces multi-peak X-ray bursts. Bult et al (2019) recently reported on a bright, Hefueled PRE Type-I X-ray burst from the accreting millisecond X-ray pulsar SAX J1808.4-3658. The light curve profile of the X-ray burst (hereafter S1) was complex: it showed a pause in the rise and a double peak unrelated to the PRE event.…”
Section: Pauses and Comparisonmentioning
confidence: 99%